The Gulf War, 1990-91 - Allison, William Thomas (Twentieth century wars, 2012)
Incorporating the latest scholarship, William Thomas Allison provides a concise overview of the origins, course and outcomes of the first Gulf War, as well as the major issues and debates. Allison also examines the relevance of this war to other twentieth-century conflicts and the ongoing situation in the region.